Targeted Therapy with Rituximab in Felty’s Syndrome: A Case Report - Heylen, Line (Bentham Open, 2012)
Felty’s syndrome is a rare, severe extra-articular manifestation of rheumatoid arthritis (RA). There is no standard therapy, and several disease-modifying antirheumatic drugs have been used with varying success. Only very few reports exist in literature on the use of biologicals in this indication and this with a variable efficacy. We report the case of a 53-year-old woman with severe refractory/partly undertreated RA who presented with Felty’s syndrome and pancytopenia, in whom treatment with rituximab led to an marked increase of red blood cells, neutrophils and thrombocytes. In addition, the RA disease activity status improved dramatically and treatment with steroids could be reduced. The current sparse literature on this topic is reviewed.